Continental margin basins in East Asia: tectonic implications of the Meso‐Cenozoic East China Sea pull‐apart basins. (22nd November 2013) - Suo, Y. H.; Li, S. Z.; Zhao, S. J.; Somerville, I. D.; Yu, S.; Dai, L. M.; Xu, L. Q.; Cao, X. Z.; Wang, P. C.
<x xml:space="preserve">Abstract</x> The East China Sea basins, located in the West Pacific Continental Margin (WPCM) since the late Mesozoic, mainly include the East China Sea Shelf Basin (ECSSB) and the Okinawa Trough (OT). The WPCM and its adjacent seas can be tectonically divided into five units from west to east, including the Min‐Zhe Uplift, ECSSB, the Taiwan–Sinzi Belt, OT, and the Ryukyu Island Arc, which record regional tectonic evolution and geodynamics. Among those tectonic units, the ECSSB and the OT are important composite sedimentary pull‐apart basins, which experienced two stages of strike‐slip pull‐apart processes. In seismic profiles, the ECSSB and the OT show a double‐layer architecture with an upper half‐graben overlapping on a lower graben. In planar view, the ECSSB and the OT are characterized by faulted blocks from south to north in the early Cenozoic and by a zonation from west to east in the late Cenozoic. The faulted blocks with planar zonation and two‐layer vertical architecture entirely jumped eastward from the Min‐Zhe Uplift to the OT during the late Cenozoic. In addition, the whole palaeogeomorphology of the ECSSB changed notably, from pre‐Cenozoic highland or mountain into a Late Eocene continental margin with east‐tilting topography caused by the eastward tectonic jumping. The OT opened to develop into a back‐arc basin until the Miocene. Synthetic surface geological studies in the China mainland reveal that the Mesozoic tectonic setting of the WPCM is an Andean‐type continental margin developing many sinistral strike‐slip faults and pull‐apart basins and the Cenozoic tectonic setting of the WPCM is a Japanese‐type continental margin developing dextral strike‐slip faults and pull‐apart basins. Thus, the WPCM underwent a transition from Andean‐type to Japanese‐type continental margins at about 80 Ma (Late Cretaceous) and a transition in topography from a Mesozoic highland to a Cenozoic lowland, and then to below sea‐level basins. Copyright © 2013 John Wiley & Sons, Ltd.